The relationship between imagery type and collective efficacy in elite and non elite athletes - Shearer, D. A.; Thomson, R.; Mellalieu, S. D.; Shearer, C. R. (Journal of Sports Science & Medicine, 2007)
This study investigated the relationship between imagery function and individual perceptions of collective efficacy as a function of skill level. Elite (n = 70) and non elite (n = 71) athletes from a number of interactive team sports completed the Sport Imagery Questionnaire (SIQ) and the Collective Efficacy Inventory (CEI). Multiple hierarchical regression analysis was then used to examine which SIQ sub-scales predicted individual perceptions of collective efficacy. For the elite sample, Motivational General-Mastery (MG-M) imagery accounted for approximately 17% of the variance in collective efficacy scores. No significant predictions were observed in the non elite sample. The findings suggest MG-M imagery as a potential technique to improve levels of collective efficacy although competitive level may moderate the effectiveness of such interventions.